Potential Deep Brain Stimulation Targets for the Management of Refractory Hypertension - Ems, Raleigh; Garg, Anisha; Ostergard, Thomas A.; Miller, Jonathan P. (Frontiers in Neuroscience, 2019)
Hypertension is the single greatest contributor to human disease and mortality affecting over 75 million people in the United States alone. Hypertension is defined according to the American College of Cardiology as systolic blood pressure greater than 120 mm Hg and diastolic blood pressure above 80 mm Hg measured on two separate occasions. While there are multiple medication classes available for blood pressure control, fewer than 50% of hypertensive patients maintain appropriate control. In fact, 0.5% of patients are refractory to medical treatment which is defined as uncontrolled blood pressure despite treatment with five classes of antihypertensive agents. With new guidelines to define hypertension that will increase the incidence of hypertension world-wide, the prevalence of refractory hypertension is expected to increase. Thus, investigation into alternative methods of blood pressure control will be crucial to reduce comorbidities such as higher risk of myocardial infarction, cardiovascular accident, aneurysm formation, heart failure, coronary artery disease, end stage renal disease, arrhythmia, left ventricular hypertrophy, intracerebral hemorrhage, hypertensive enchaphelopathy, hypertensive retinopathy, glomerulosclerosis, limb loss due to arterial occlusion, and sudden death. Recently, studies demonstrated efficacious treatment of neurological diseases with deep brain stimulation for Tourette’s, depression, intermittent explosive disorder, epilepsy, chronic pain, and headache as these diseases have defined neurophysiology with anatomical targets. Currently, clinical applications of deep brain stimulation is limited to neurological conditions as such conditions have well-defined neurophysiology and anatomy. However, rapidly expanding knowledge about neuroanatomical controls of systemic conditions such as hypertension are expanding the possibilities for DBS neuromodulation. Within the central autonomic network, multiple regions play a role in homeostasis and blood pressure control that could be DBS targets. While the best defined autonomic target is the ventrolateral periaqueductal gray matter, other targets including the subcallosal neocortex, subthalamic nucleus, posterior hypothalamus, rostrocaudal cingulate gyrus, orbitofrontal gyrus, and insular cortex are being further characterized as potential targets. This review aims to summarize the current knowledge regarding neurologic contribution to the pathophysiology of hypertension, delineate the complex interactions between neuroanatomic structures involved in blood pressure homeostasis, and discuss the potential for using DBS as a treatment for refractory hypertension.